PENERAPAN IPTEKS UNDANG-UNDANG NOMOR 10 TAHUN 2020 TENTANG BEA MATERAI - Tri Yanuaria; Kadir Katjong; Dudi Mulyadi (LPPM Uncen, 2023)
This service is carried out under the title Application of Science and Technology, Law Number 10 of 2020 concerning Stamp Duty. The partners in this service are lecturers and students at Muhammadiyah Papua University, with the aim that lecturers and students have knowledge and skills regarding the application of Law Number 10 Year 2020 regarding Stamp Duty. Stamp duty is a label or strip in the form of a sticky, electronic, or other form that has characteristics and contains a security element issued by the Government of the Republic of Indonesia, which is used to pay tax on Documents. The application of science and technology to Law Number 10 of 2020 concerning Stamp Duty is carried out on Tuesday, June 14 2022, activities starting from 1). Preparation, work program, coordination; 2). presentation of the material. The method of implementing this service is carried out by way of lectures, discussions, questions and answers related to the function of stamp duty, documents that do not need to be given stamp duty, documents that must be given stamp duty, legal sanctions in violating the Stamp Duty Law, taking into account the protocol covid-19. as well. The output of this service is an increase in partners' knowledge about the function of stamp duty, about documents that do not need to be given stamp duty, about documents that must be given stamp duty Knowledge of legal sanctions in violating the Stamp Duty Law, in accordance with the Mandate of Law No. 10 of 2020 Regarding Stamp Duty.Ã‚Â Keywords: Law; Number 10 of 2020; Regarding; Stamp Duty